Communication across autism, ADHD, and non-clinical groups: examining autistic and ADHD traits from a dimensional perspective - Ramona Cardillo; Rachele Lievore; Enrico Toffalini; Giulia Crisci; Irene Cristina Mammarella (Frontiers in Psychology, 2026)
Introduction Communication difficulties are common among youth with Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD). However, traits associated with ASD and ADHD are continuously distributed in the general population, raising the question of how communication differences are better described when considering both diagnostic categories and dimensional trait variation. Methods This study included 493 Italian children and adolescents aged 7–16 years old ( M = 11.35; SD = 2.64): 147 (126 boys) with ASD without intellectual disability, 105 (88 boys) with ADHD, and 241 (203 boys) non-diagnosed (ND) peers. Parents completed standardized measures assessing communication skills, ASD and ADHD traits. Results Both clinical groups showed significant communication difficulties compared to ND peers, with large effect sizes (ASD-ND: d = −1.67; ADHD-ND: d = −1.00). In this dataset, communication outcomes were more parsimoniously modelled using continuous ASD and ADHD trait measures (BIC = 4151.39) than diagnostic group membership alone (BIC = 4324.75). Both trait dimensions were associated with communication challenges across clinical and non-diagnosed participants, although the association with ADHD traits was weaker. Discussion These findings suggest that communication difficulties may be usefully described in relation to continuous ASD and ADHD trait variation, while preserving the clinical relevance of diagnostic categories.